Impacts of Fisheries Harvesting on Fish-Bird Model for the Salton Sea Region - Kumar, Bipin; Sinha, Rajesh Kumar; Kumar, Amit (Communications in Mathematics and Applications, 2024)
This study investigates the impact of fisheries harvesting on a Fish-bird model, focusing specifically on the presence of illnesses in fish and the consequential effects on bird populations. Tilapia fish, serving as the primary dietary source for pelican birds in the Salton Sea region, face the risk of overexploitation due to increased fishing activities. The study reveals that heightened harvesting rates can lead to the eventual extinction of bird species over time, highlighting the delicate balance between fishing sustainability and ecological preservation. The equilibrium and stability of the system are analyzed, with numerical simulations illustrating various dynamical behaviors such as chaotic attractors and quasi-periodic oscillations. The harvesting model considers the extraction of both susceptible and infected fish, demonstrating that an increase in the harvesting rate of susceptible fish poses a significant threat to bird populations. Conversely, while maintaining a constant harvesting rate of infected fish, the bird population remains viable even for varying levels of infected harvesting rates. Ultimately, the study underscores the importance of sustainable fishing practices, cautioning against the overexploitation of susceptible fish, which could lead to the extinction of birds in the Salton Sea region.
Keywords: Fish-bird model; Harvesting; Local stability analysis; Chaotic attractor; Quasi periodic ascillation